FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN APLIKASI ANALISIS INVESTASI MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL - Jefri Ilham Rachmawan; Nurlita Novianti (TEMA, 2021)
This study aims to predict and explain TAM indicators on the use of investment analysis applications by investors in East Java. The application under study was made by Kompas Gramedia Group, namely RTI Business. This type of research is quantitative research by distributing questionnaires. The sample in this study was obtained using non-probability sampling method. The subject of this research is investors who live in East Java who have used the RTI Business application with a total of 186 respondents. The analytical method used is regression analysis using SPSS version 25. The results of this study indicate that perceptions of convenience and perceptions of usefulness have a positive effect on interest in using. Furthermore, interest in using has a positive effect on use. In addition, interest in using succeeded in partially mediating the effect of perceived ease and perceived usefulness on usage. This means that the perception of convenience and the perception of usefulness can affect the use either directly or indirectly with the role of interest in using it as a mediation.